Tooth Impaction and Hypodontia in a Patient with Talon Cusp: Report of a Case - Bagheri, Fatemeh; Barakian, Yasamin (Journal of Dental School, 2018)
Objectives This study is aimed to introduce an unusual case of a female with two talon teeth on both maxillary lateral incisors. Case A 38-year-old female was referred to oral medicine department, Qom university of medical sciences for routin examinations. Bilateral maxillary talon cusp was observed on maxillary lateral incisors. Future evaluation revealed impaction of maxillary left canine and missing all wisdom teeth. Since talon teeth were not decayed and no occlusal interferences were present, no treatment was performed and patient was scheduled for routine follow up recalls. Conclusion Comprehensive examination of the case revealed the province of bilateral talon cusp teeth in maxilla